(untitled) (Global Journal of Management and Business Research, 2016)
Wasiyyah or will is a legal document that outlines on how one#x2019;s estate is to be distributed in the event of affairs after the death of the testator according to Islamic law. Recently, the abundance of wasiyyah property is getting increase year by year resulting the accumulation of these properties without proper distribution among the testator#x2019;s beneficiary. Consequently, this wasiyyah caused detrimental to the testators#x2019; beneficiaries and indirectly indicates the failure to fully understand the whole concept of Islamic property management via wasiyyah. On top of that, the confusion between wasiyyah, hibah, waqf and other Islamic property management might also lead to the above situation. This study therefore will further examine the concept and the conditions of wasiyyah and provide the procedure involved in the documentation of wasiyyah with special reference to As-Salihin Trustee, one of renowned wills Management Company in Malaysia.